(untitled) (American Journal of Islam and Society, 1989)
The paper is incomplete in its present form. Its discussion about Islamic Ethics is superficial. Neither the complexity of theological ethics nor are philosophical and juridical ethics admitted anywhere. Moreover, it does not evaluate the present status of works on ethics (e.g., Isma’il al Faruqi’s contribution) and the scholarship produced by academics like Hourani (The Ethics of ’Abd Al-Jabbar). The paper must be expanded with proper discussion about the conceptual difficulties and the Islamic alternative. Certainly there is a need for this discussion, but not so superficially ...